Bridging the skills gap: apprentice assistant practitioners having an impact in mental healthcare services. Part 4. The practice trainer experience. Issue 2 (2nd February 2022) - Beard, Alison; Miller, Tracy; Morris, Andy
Abstract : In understanding the impact of apprentice assistant practitioners (AAPs) on mental healthcare services, it is important to understand the role of the practice trainer (PT). This article is the last in a series of four looking at AAPs in mental healthcare services. It will focus on the experiences of the PTs as they support AAPs working towards their qualified AAP role. The challenges faced by mental healthcare services and the role of the PT in supporting workforce development via the AAPs will be introduced. Semi-structured interviews were carried out on two PTs working in the north west of England and employed at the University of Bolton. Both participants work with AAPs employed in mental healthcare services and consented to take part. During the interview, the PTs were asked to outline how long they had worked in role, followed by an exploration into their experiences of supporting AAPs within mental healthcare services. The PTs were asked to give their opinion on the development of their role, throughout the programme, with particular reference to the restrictions and changes COVID-19 had made to their role.